Pengaruh Persepsi Manfaat Dan Persepsi Keamanan Terhadap Niat Menggunakan Melalui Kepercayaan Konsumen Pada Aplikasi Dompet Digital DANA - Ainun Hikmah; RA Nurlinda (Universitas 45 Surabaya, 2023)
This research is a quantitative research with a causal relationship to determine whether there is a direct effect of perceived benefits, perceived safety on consumer confidence, knowing the direct effect, perceived safety, customer trust on the intention to use. As well as knowing the indirect effect of perceived benefits, perceived security perceptions on intention to use through consumer trust in the DANA digital wallet application. Data collection was carried out by collecting information through a survey with a questionnaire. The population in this study is someone who already knows the DANA digital wallet application in the Greater Jakarta area. The questionnaire collected 130 respondents using the Hair et al., (2017) formula. The sampling method used is non-probability sampling with purposive sampling technique. Based on the research results, of the 7 accepted hypotheses, namely perceived benefits and perceived safety affect consumer confidence. Perceived benefits and consumer trust influence the intention to use. While the perception of security has no effect on the intention to use. The contribution of this study results in the intention to use with the influencing factors, namely the perceived benefits and consumer confidence in the intention to use. Therefore, it is important for the DANA Application to increase the benefits and safety because consumers who have high trust in technology can increase their intention to use the technology.